Reassessing reform : a historical investigation into church renewal - Bellitto, Christopher M.; Flanagin, David Zachariah (Catholic University of America Press, 2012)
"At the conclusion of his definitive study The Idea of Reform, which carved out reform as a distinct field of intellectual history, Gerhart Ladner stated that the idea of reform was "to remain the self-perpetuating core, the inner life spring of Christian tradition through lesser and greater times." Ladner himself sought to explore patristic theology and early Christian monasticism and his insights laid the groundwork for a half-century of scholarship. Now, in celebration of the 50th anniversaries of the publication of The Idea of Reform and the Second Vatican Council, Reassessing Reform explores and critiques the enduring significance of Ladner's study, surveying new avenues and insights of more recent reform scholarship, especially concerning the long Middle Ages. Contributors aim to reassess Ladner's historical and theological examination of the idea of reform in the Christian tradition, with a special focus on its meaning from the end of the patristic age to the dawn of modernity, through case studies and historiographical assessments. Many of the authors are not only scholars of history, but they also work intimately with church reform in their own everyday professional and faith lives."--Publisher's description.